(untitled) - Oboler, Suzanne (Minneapolis, 1995)
In Ethnic Labels, Latino Lives, Suzanne Oboler explores the history and current use of the label "Hispanic" as she explodes the myth of cultural and national homogeneity among people of Latin American descent. She discusses the historical process of labeling groups of individuals, and illustrates how ethnic labels affect the meaning of citizenship and the struggle for full social participation in the United States.
Keywords: Hispanic Americans,Hispanic Americans; Ethnic identity,Name